Effects of fiscal deficit and money M2 supply on inflation: Evidence from selected economies of Asia - Nguyen, Van Bon (2015)
A sustained high growth rate of gross domestic product at a low inflation is one of the main goals of the majority of macroeconomic policies, so keeping the price stability plays an important role in determining the growth rate of output. This paper empirically investigates effects of fiscal deficit and broad money M2 supply on inflation in Asian countries, namely Bangladesh, Cambodia, Indonesia, Malaysia, Pakistan, Philippines, Sri Lanka, Thailand, and Vietnam in the period of 1985-2012. By applying the Pooled Mean Group (PMG) estimation-based error correction model and the panel differenced GMM (General Method of Moment) Arellano-Bond estimator, the study finds out broad money M2 supply has significantly positive impact on inflation only in the method of PMG estimation whereas fiscal deficit, government expenditure and interest rate are the statistically significant determinants of inflation in both methods of estimation. Doi: http://dx.doi.org/10.1016/j.jefas.2015.01.002